Long‐term evaluation (20 years) of the outcomes of coronally advanced flap in the treatment of single recession‐type defects. Issue 3 (12th March 2018) - Pini Prato, Giovan Paolo; Magnani, Cristina; Chambrone, Leandro
Abstract: Background: Coronally advanced flap (CAF) has been considered as one of the most predictable and versatile root coverage procedures. Thus, the aims of this study are two‐fold: 1) to evaluate the long‐term outcomes following CAF in the treatment of gingival recession (GR); and 2) to explore the influence of several tooth/patient‐related factors on the stability of gingival margin at 5, 10, and 20 years after surgery. Methods: Ninety‐four patients with 97 GR (73 Miller`s Class I and 24 Miller's Class III) were treated with CAF in a private practice between 1984 and 1996. Recession depth (RD), probing depth (PD), keratinized tissue (KT) width and patient/tooth‐associated variables were recorded for each GR at baseline, 1 year, 5 years, 10 years, 15 years and 20 years after surgery. Parametric, non‐parametric, and logistic regression statistics were used throughout the study Results: A total of 72 patients with 72 GR were available for analysis at the 20‐year follow‐up examination (final patients' dropout rate = 23.4%). Statistically significant improvements were found for RD in all evaluations ( P  < 0.05). Little more than a half (56%) of the sites treated with CAF did not display RD changes between the short‐term (i.e., 1 year) and long‐term (i.e., 20 years) examinations. Overall, mean root coverage (MRC) decreased from 68.59% to 56.11%. The achievement of complete root coverage (CRC) 1 year after treatment was associated to GR not presenting interdental tissue loss ( P  = 0.001), the root condition (i.e., lack of non‐carious cervical lesion [step] – P  < 0.001), an attached KT band ≥ 2 mm ( P  = 0.019), and baseline RD ( P  = 0.020). GR recurrence seemed to be influenced by age, RD at 1‐year follow‐up, sites displaying an attached KT < 2 mm and interdental tissue loss. Conclusions: The aging process, the condition of the interdental periodontal tissue, and the presence of an attached KT band < 2 mm seem to be negative factors influencing the stability of the gingival margin during the 20‐year observation period.